On the Sign of Solutions of Systems of Ordinary Differential Equations - Kalinowski, J. (Український математичний журнал, 2002)
We show that Theorems 1 and 3 in A. G. Gritsai's paper “Monotonicity properties of solutions of systems of nonlinear differential equations” published in the collection of works Approximate and Qualitative Methods in the Theory of Differential and Functional Differential-Equations (Institute of Mathematics, Ukrainian Academy of Sciences, Kiev, 1979) are not true in the formulation presented.